Effects of Fermented Oat Straw as a Lovastatin Carrier on in vitro Methane Production and Rumen Microbiota - Ábrego-Gacía, Amaury; Poggi-Varaldo, Héctor M.; Mendoza-Vargas, Alfredo; Mercado-Valle, Francisco G.; Ríos-Leal, Elvira; Ponce-Noyola, Teresa; Calva-Calva, Graciano (Frontiers in Energy Research, 2021)
To date, there is an urgent need for implementing practical strategies to reduce CH4 emissions from ruminants. Lovastatin (Lv) is a specific inhibitor of methanogenic archaea. Due to the high cost of Lv, solid-state fermentation might be an economical bioprocess to produce it and facilitate its use in ruminant nutrition.We assessed the effects of supplementing fermented oat straw as a lovastatin-carrier (FOS) to a high-grain ration on in vitro CH4 inhibition and rumen microbiota in beef cattle. The experimental design was completely randomized with four concentrations of Lv in the diet mixture. The supplementation with FOS to give Lv concentration of 100 and 150 mg L-1 in the ruminal fermentation medium significantly inhibited methanogenesis at similar levels. This suggested that less than 20% of FOS was required in the ration to achieve up to 38 % of CH4 mitigation without affecting the chemical composition and nutritional value of the ration. Short-chain fatty accidents (SCFA) production and profile showed that only the treatments with Lv at 100 and 150 mg L-1 decreased the concentration of total SCFA; the molar ratio of propionate significantly increased with respect to that of the control. The treatment with Lv at 150 mg L-1 did not result in significant differences in the alpha and beta diversity indices compared to the control. However, significant changes in the relative abundance of some microorganisms were detected, such as an increase in Ruminococcus, and a decrease in Prevotella. Comment 45 The predominant 99%+ MA in all controls, treatment, and inocula samples belonged to the Methanobrevibacter genus and very small (negligible) unclassified Methanobacteria genus (Euryarchaeota phylum). Interestingly, the reduction of relative abundance of MA was 39.17%, very close to the percent reduction of CH4 production, 38%. Our data showed that there was a parallel and similar percent decrease of both CH4 production and relative abundance of the predominant MA in our experiment, although the statistical significance was not complete. Comment 28. Finally, our results hold promise for significantly decreasing ruminal CH4 by 38 %. Thus, our work is one step towards the sustainable management of the livestock sector.